Cell therapy in orthopaedics: where are we in 2019?. (April 2019) - Rodeo, S. A.
Abstract : Stem cells are defined by their potential for self-renewal and the ability to differentiate into numerous cell types, including cartilage and bone cells. Although basic laboratory studies demonstrate that cell therapies have strong potential for improvement in tissue healing and regeneration, there is little evidence in the scientific literature for many of the available cell formulations that are currently offered to patients. Numerous commercial entities and 'regenerative medicine centres' have aggressively marketed unproven cell therapies for a wide range of medical conditions, leading to sometimes indiscriminate use of these treatments, which has added to the confusion and unpredictable outcomes. The significant variability and heterogeneity in cell formulations between different individuals makes it difficult to draw conclusions about efficacy. The 'minimally manipulated' preparations derived from bone marrow and adipose tissue that are currently used differ substantially from cells that are processed and prepared under defined laboratory protocols. The term 'stem cells' should be reserved for laboratory-purified, culture-expanded cells. The number of cells in uncultured preparations that meet these defined criteria is estimated to be approximately one in 10 000 to 20 000 (0.005% to 0.01%) in native bone marrow and 1 in 2000 in adipose tissue. It is clear that more refined definitions of stem cells are required, as the lumping together of widely diverse progenitor cell types under the umbrella term 'mesenchymal stem cells' has created confusion among scientists, clinicians, regulators, and our patients. Validated methods need to be developed to measure and characterize the 'critical quality attributes' and biological activity of a specific cell formulation. It is certain that 'one size does not fit all' – different cell formulations, dosing schedules, and culturing parameters will likely be required based on the tissue being treated and the desired biological target. As an alternative to the use of exogenous cells, in the future we may be able to stimulate the intrinsic vascular stem cell niche that is known to exist in many tissues. The tremendous potential of cell therapy will only be realized with further basic, translational, and clinical research. Cite this article: Bone Joint J 2019;101-B:361–364.